Identifikasi Struktur Komponen Senyawa Kimia Kulit Batang Ketapang (Terminalia catappa L.) - Edi Ilimu; Alimuddin; Ruslin Hadanu; Nurfianti (Jurnal Ilmiah Kanderang Tingang, 2023)
Ketapang (Terminalia catappa L.) is a type of flowering plant that has been widely used by the community, especially in traditional medicine. This research aims to identify the chemical compound components of Ketapang bark using Virgin Coconut Oil (VCO) solvent. Research methods include making VCO, maceration extraction, solubility testing, identification of chemical compound components using FTIR and GC-MS. The mass of VCO is 744.32 grams (14.88% soaking). The mass of Ketapang bark extract weighed 183.88 grams (0.63% soaking). The solubility test shows that VCO and extracts are generally nonpolar. Identification results using FT-IR show that VCO has C-H, C=O and C-O groups, while ketapang bark extract has aliphatic –CH, C=O, C-O, C-OH, C-N and aromatic C-H groups. Identification using GC-MS showed that VCO had 112 peaks, among the 112 peaks that had a similarity index of 80% there were 14 peaks, while the ketapang bark extract had 190 peaks and 11 peaks had a similarity index. Thus, it can be concluded that the components of the VCO compound are decanoic acid, dodecanoic acid, tridecanoic acid, myristic acid, pentadecanoic acid, 2-monocaprin (2TMS derivative), palmitelaidic acid, palmitic acid, and stearic acid. Meanwhile, Ketapang stem bark extract contains heptadecanoic acid, (z) oleic acid, elaidic acid, 1-ethoxy-4'-methoxy-2,2'-binaptyl-1,4-dione, eikosan, 7-methyl-z-tetradeken- 1-ol-acetate, beta-alanine, sarcosine, 1-aminomethyl-cyclododecanol, and dodecanoic acid, 2,3-dihydroxypropyl ester.